Intentional Switching Between Bimanual Coordination Patterns in Older Adults: Is It Mediated by Inhibition Processes? - Temprado, Jean-Jacques; Torre, Marta Maria; Langeard, Antoine; Julien-Vintrou, Marine; Devillers-Réolon, Louise; Sleimen-Malkoun, Rita; Berton, Eric (Frontiers in Aging Neuroscience, 2020)
The study investigated the consequences of age-related decline in inhibition processes on intentional switching between bimanual coordination patterns. Fifteen young (24±2.8 years) and 20 older adults (69±5.3 years) performed Stroop tasks and bimanual coordination tasks. Stroop tasks included neutral, congruent, and incongruent conditions. Response time and error rate were measured. Bimanual coordination tasks consisted of performing in-phase (IP) and anti-phase (AP) patterns. Participants were requested to switch as quickly as possible from one pattern to the other, resulting in two different switching directions (AP to IP; IP to AP). Mean and standard deviation (SD) of the continuous relative phase (CRP) were calculated pre- and post-switching for each participant. Total switching time (TST) was measured. The switching phase was also decomposed into reaction time (RT) and reversal time (REvT). Pearson correlation analyses were performed to test for correlations between: (i) SD of CRP and response time in Stroop tasks, and (ii) switching times (TST, RT, RevT) and response time in Stroop task, respectively. In addition, parallel mediation analyses were conducted. Results showed that: (i) the AP pattern was less stable than the IP pattern in both young and older adults, (ii) coordination patterns were less stable in older adults, (iii) response times in Stroop task were longer in the incongruent condition, and (iv) RespTs were longer in older than in young participants, whatever the condition. In the bimanual coordination task, RT, RevT, and TST increased with age. The stability of the IP pattern was correlated with the response times observed in neutral and congruent conditions, while the stability of the AP pattern was correlated with response time observed in the incongruent condition. Correlation and mediation analyses showed that, in the AP to IP switching direction, RT and RevT were both significantly correlated with response times observed in the incongruent condition of Stroop task. These findings suggest that inhibition processes are involved in switching between bimanual coordination patterns, at least to trigger the early phase of switching. They also support the hypothesis that inhibition processes are more involved in maintaining the AP pattern and switching to the IP pattern. Finally, age-related changes in switching times seem to be prominently mediated by alterations of inhibition processes.